Leveraging TikTok for Enhanced Digital Marketing and Consumer Engagement: Memanfaatkan TikTok untuk Meningkatkan Pemasaran Digital dan Keterlibatan Konsumen - Rahmah, Eva Zulfiatur; Rangga, Moch Devan; Syaro , M Fandi; Rahmayanti, Vivia Nailur; Cahyana, Atikha Sidhi (Universitas Muhammadiyah Sidoarjo, 2024)
This study explores the increasing utilization of digital platforms for marketing, focusing on the TikTok application due to its burgeoning popularity across diverse demographics. The research employs a mixed-methods approach, analyzing both quantitative usage data and qualitative consumer feedback to assess the effectiveness of online promotions through TikTok. Results demonstrate that TikTok's accessibility and widespread adoption significantly enhance product visibility and consumer engagement, leading to increased sales. Furthermore, the convenience of shopping via this platform saves time and energy for consumers, highlighting a shift in purchasing patterns. The implications of these findings suggest that businesses can leverage TikTok to tap into a broader market, potentially reshaping traditional marketing strategies and consumer interaction in the digital age. Highlights: Online promotions via TikTok are gaining popularity due to widespread usage and accessibility. Shopping online saves time and energy by eliminating the need to visit physical stores. Utilizing platforms like TikTok for marketing offers a dynamic and engaging way to reach potential customers. Keywords: Online Shop, Utility, Dynamic System, Simulation